Non-prescription proton-pump inhibitors for self-treating frequent heartburn: the role of the Canadian pharmacist - Armstrong D; Nakhla N (Pharmacy Practice, 2016)
Heartburn and acid regurgitation are the cardinal symptoms of gastroesophageal reflux and occur commonly in the Canadian population. Multiple non-prescription treatment options are available for managing these symptoms, including antacids, alginates, histamine-H2 receptor antagonists (H2RAs), and proton-pump inhibitors (PPIs). As a result, pharmacists are ideally positioned to recommend appropriate treatment options based upon an individual’s needs and presenting symptoms, prior treatment response, comorbid medical conditions, and other relevant factors. Individuals who experience mild heartburn and/or have symptoms that occur predictably in response to known precipitating factors can manage their symptoms by avoiding known triggers and using on-demand antacids and/or alginates or lower-dose non-prescription H2RAs (e.g. ranitidine 150 mg). For those with moderate symptoms, lifestyle changes, in conjunction with higher-dose non-prescription H2RAs, may be effective. However, for individuals with moderate-to-severe symptoms that occur frequently (i.e. ≥2 days/week), the non-prescription (Schedule II) PPI omeprazole 20 mg should be considered. The pharmacist can provide important support by inquiring about the frequency and severity of symptoms, identifying an appropriate treatment option, and recognizing other potential causes of symptoms, as well as alarm features and atypical symptoms that would necessitate referral to a physician. After recommending an appropriate treatment, the pharmacist can provide instructions for its correct use. Additionally, the pharmacist should inquire about recurrences, respond to questions about adverse events, provide monitoring parameters, and counsel on when referral to a physician is warranted. Pharmacists are an essential resource for individuals experiencing heartburn; they play a crucial role in helping individuals make informed self-care decisions and educating them to ensure that therapy is used in an optimal, safe, and effective manner.